2014
DOI: 10.5530/ijopp.7.3.12
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Prescribing Pattern of Cirrhosis in a Tertiary Care Hospital

Abstract: Liver cirrhosis is one of the major non communicable diseases, which is expected to be a prime health care concern of the 21 st century. In the present world, the number of persons suffering from the liver disorders is increasing. This may be due to the change in lifestyle and many stress related factors. Identification of the demography of patients with cirrhosis is of great importance in the current health care scenario for the calculation of prevalence of this frustrating disease. The aim of the study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…In a study by Vijayan M et.al in Kerala topical emollients, topical steroids and antihistaminics were the 3 common types of drugs administered to psoriatic patients. [13] In the present study nearly 16% of the psoriatic patients were found to be diagnosed with hypertension. Psoriasis was found to be associated with hypertension in a study by Ghiasi M et al [26] Few other studies also showed similar association.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In a study by Vijayan M et.al in Kerala topical emollients, topical steroids and antihistaminics were the 3 common types of drugs administered to psoriatic patients. [13] In the present study nearly 16% of the psoriatic patients were found to be diagnosed with hypertension. Psoriasis was found to be associated with hypertension in a study by Ghiasi M et al [26] Few other studies also showed similar association.…”
Section: Discussionmentioning
confidence: 75%
“…[23] Different studies from India and abroad have found chronic plaque psoriasis as the commonest variety of psoriasis. [7,13,16,17] Majority (50%) of patients had severe grade of psoriasis as per PASI scoring (>20) and only 8% had mild grade of psoriasis. In a study done by Gopal MG et.al, in Bangalore 42% had severe grade of psoriasis and 3% had mild grade of psoriasis as per PASI scoring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol consumption for a period of 6-10 years 36 people were highly affected with ALD (23.68%) followed by [11][12][13][14][15] The major co-morbidity in ALD patients was Hypertension (15, 41%), followed by Diabetes mellitus (15, 40%), CVA (4, 11%) and Bronchial asthma (3, 8%). Under the category of diuretics Furosemide-113 (50.22%) followed by Aldactone -107 (47.55%), Metalazone-3 (1.33%) and Prazosin -2 (0.8%) were major diuretic agents to treat ALD complications.…”
Section: Resultsmentioning
confidence: 99%
“…These findings were similar to Meenu Vijayan study. 12 The most common cause of portal hypertension is cirrhosis of liver. Cirrhosis is scarring which accompanies the healing of liver injury caused by hepatitis, alcohol, or other causes of liver damage.…”
Section: Discussionmentioning
confidence: 99%